2003
DOI: 10.1034/j.1399-0012.2003.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in renal transplant recipients: epidemiology, predictive risk factors and outcome

Abstract: Prevalence of stroke in our RTR population was 7.97%. Cerebral hemorrhage appears to be more prevalent in RTR than in general population. More than that, the cerebral hemorrhage rate we found is higher than that reported elsewhere in RTR. The main predictors of stroke were DN, PVD and age. No patient with interstitial nephropathy suffered stroke. Mortality is high in RTR with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
50
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 22 publications
9
50
1
Order By: Relevance
“…5 Similarly, several prior studies have described associations between hypertension and the development of CVD in kidney transplant recipients. 4,[32][33][34] Our findings reinforce these conclusions in a population with detailed ascertainment of CVD, further demonstrating that there is no notable J-shaped association between systolic BP level and cardiovascular or mortality outcomes. This study has several limitations.…”
Section: Discussionsupporting
confidence: 78%
“…5 Similarly, several prior studies have described associations between hypertension and the development of CVD in kidney transplant recipients. 4,[32][33][34] Our findings reinforce these conclusions in a population with detailed ascertainment of CVD, further demonstrating that there is no notable J-shaped association between systolic BP level and cardiovascular or mortality outcomes. This study has several limitations.…”
Section: Discussionsupporting
confidence: 78%
“…Observation time was censored at Vertebrobasilar syndrome 435. 8 Other specified transient cerebral ischemia 435. 9 Other nonspecified transient cerebral ischemia transplantation for incidence computations among transplant candidates; similarly, at-risk time was ended at graft failure for incidence computations among transplant recipients.…”
Section: Definitions Of Outcomes and Covariates Cve And At-risk Periodsmentioning
confidence: 99%
“…Counts of observed cases of CVE in published studies have ranged from 19 (4.7%) of 402 prevalent diagnoses in a cross-sectional study of Spanish transplant patients (8) to 48 and 54 events among variably followed cohorts of 922 and 675 American transplant recipients (9,10), respectively. With respect to CVE types, the study of prevalent CVE among Spanish recipients identified seven (37%) of 19 diagnoses as hemorrhagic, but published cohort studies after transplantation have either not included hemorrhagic events in the outcome definition (10) or not distinguished CVE types in results reporting (9).…”
mentioning
confidence: 99%
“…Oliveras and colleagues observed a 10-year incidence rate of stroke at 8.0% in their single-center analysis of 403 patients, with nearly a 50% mortality risk within 3 months after the stroke. 4 Aull-Watschinger and colleagues observed 54 strokes (and 10 transient ischemic attacks) among 1633 recipients transplanted between 1995 and 2005 (incidence, 3.9%), of which 19 were fatal. 5 De Mattos and colleagues observed 48 stroke-related events (39 strokes, 6 transient ischemic attacks, and 3 carotid endarterectomies) in a cohort of 922 kidney allograft recipients who received a transplant between 1993 and 1998 (incidence, 5.2%), with 17 stroke-related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Oliveras and colleagues observed a 10-year incidence rate of stroke at 8.0% in their single-center analysis of 403 patients, with nearly a 50% mortality risk within 3 months after the stroke. 4 Renal Data System, they found a 3-year incidence of de novo stroke at 6.8% (lower than estimates on the waiting list or after graft loss). To our knowledge, no other study has been conducted at a population level to evaluate the effect of stroke-related events (fatal and nonfatal) in the context of kidney transplant; this represents a major gap in the literature.…”
mentioning
confidence: 99%